Complementary and alternative therapies for poststroke depression: A protocol for systematic review and network meta-analysis. Issue 38 (18th September 2020) - Song, Kai; Xiong, Fanjie; Wang, Yating; Wang, Haiyan; Huang, Ailing; Zhang, Hong
Abstract: Background: Poststroke depression (PSD) is an important complication of stroke, resulting in increased disability and mortality, which is a great threat to stroke survivors and public health. Complementary and alternative medicine (CAM) therapies is widely used in the treatment of PSD, However, the selection strategies of different CAM approaches in clinical practice is still not clear, and the purpose of this protocol is to compare the efficacy and acceptability of different CAM therapies using systematic review and network meta-analysis. Methods: According to the strategy, the authors will retrieve a total of seven electronic databases by August 2020, including PubMed, the Cochrane Library, EMbase, China National Knowledge Infrastructure, China Biological Medicine, Chinese Scientific Journals Database, and Wan-fang databases. The network meta-analysis will be performed using Aggregate Data Drug Information System 1.16.8 and Stata 13.0 software. In addition, the Cochrane Collaboration's tool is employed for the methodological quality, and the quality of evidence will be evaluated according to the Grading of Recommendations Assessment, Development, and Evaluation system. Results: This study will provide a reliable evidence for the selection strategy of CAM therapies for PSD. Conclusion: The results of this study will provide references for evaluating the effects of different CAM therapies on PSD, and provide decision-making references for clinical practitioners, patients, and health policy makers. Ethics and dissemination: This study does not require ethical approval. the results will be disseminated through a peer-reviewed publication. OSF registration number: DOI 10.17605/OSF.IO/TNGH6.